2017
DOI: 10.7589/2016-03-058
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Cysticercosis in a Red Fox (Vulpes vulpes)

Abstract: A large abdominal mass containing numerous cysticerci identified as those of Taenia crassiceps (=Cysticercus longicollis) was found in the pelvic region of the abdominal cavity of a severely constipated and emaciated red fox ( Vulpes vulpes ) in Prince Edward Island, Canada. Cysticercosis has not previously been reported in a wild canid in North America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…After eating an infected intermediate host, the cysticerci develop into their adult stages in the small intestine of the definitive host [ 2 ]. Noteworthily, animals serving as definitive hosts can also suffer from cysticercosis by C. longicollis, which was reported in several studies [ 4 , 6 , 7 , 8 , 9 ]. A variety of routes of exposure resulting in cysticercosis have been postulated, such as autoinfection via eggs from the host’s feces, or eggs from the environment.…”
Section: Introductionmentioning
confidence: 94%
“…After eating an infected intermediate host, the cysticerci develop into their adult stages in the small intestine of the definitive host [ 2 ]. Noteworthily, animals serving as definitive hosts can also suffer from cysticercosis by C. longicollis, which was reported in several studies [ 4 , 6 , 7 , 8 , 9 ]. A variety of routes of exposure resulting in cysticercosis have been postulated, such as autoinfection via eggs from the host’s feces, or eggs from the environment.…”
Section: Introductionmentioning
confidence: 94%
“…Sporadic cases of cysticercosis caused by T. crassiceps have been documented in humans (Table 2), non-human primates (Tabel 4), but also rarely in e.g. domestic dogs (Ballweber, 2009; Beugnet et al, 2009; Chermette et al, 1993; Hoberg et al, 1999), a cat (Wunschmann et al, 2003), red foxes (Konjević et al, 2016; Whipp et al, 2017) and a chinchilla ( Chincilla lanigera ) (Basso et al, 2014).…”
Section: Canid-transmitted Cysticercosis and Coenurosismentioning
confidence: 99%
“…As a consequence, severe cysticercosis can develop in intermediate hosts, leading to a fatal outcome. Several studies reported that carnivores such as dogs, cats, and foxes can also develop cysticercosis caused by C. longicollis , presuming that immunocompromised status was the main cause of disease occurrence [ 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%